SISTEM PENDUKUNG KEPUTUSAN IZIN MENDIRIKAN BANGUNAN - Irma T (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
System of Supporter of Decision of Permit Gift Found the Building represent an application program the computerization which can facilitate the work moderation in decision making (decision making) by Government of Town Makassar of about publication IMB (Permit Found the Building) fixed relate at regulation - governmental regulation of town makassar of about gift or publication of letter IMB (Permit Found the Building and settlement of space of town makassar. This matter is enabled by because this system own various assessment criterion of at IMB obtained and formulated by paying attention to a lot of factor assumed relevant and need, Is hereinafter modeled mathematically utilize the of a assistive assessment all decision taker in make decision the Permit Found the Building of at Government of Town Makassar